Age and granite association of skarn W mineralization at Niutangjie district, South China Block - Chen, Xilian; Liang, Huaying; Richards, Jeremy P.; Huang, Wenting; Zhang, Jian; Wu, Jing; Sotiriou, Paul (Ore Geology Reviews, 2018)
Numerous W-Sn deposits are developed in the South China Block with the majority related to the Yanshanian (Jurassic to Cretaceous) granites; a smaller number of deposits have been found associated with Kwangsian (middle Paleozoic) granites, the largest of which is the Niutangjie skarn W deposit. The Niutangjie deposit is spatially associated with two suites of granites: the unmineralized Yuechengling biotite and two-mica granites have zircon U-Pb ages of 427.1 ± 2.9 Ma and 427.5 ± 3.5 Ma, respectively, whereas the mineralized Niutangjie muscovite granite yields a younger age of 421.0 ± 1.5 Ma. U-Pb dating of cassiterite coexisting with scheelite from the Niutangjie muscovite granite indicates a mineralization age of 420.8 ± 8.0 Ma, consistent with the age of the host rock. The unmineralized Yuechengling biotite granites have A/CNK ratios of 0.97–1.16 and show characteristics of both I-type and S-type granites. In contrast, the mineralized Niutangjie muscovite granites are S-type granites with A/CNK ratios of 1.12–1.72 and have higher SiO2 contents and Rb/Sr ratios, and lower Nb/Ta, Zr/Hf, and K/ Rb ratios than the unmineralized Yuechengling biotite granites. Geochemical differences together with zircon Hf isotopic compositions indicate that the relatively fractionated mineralized Niutangjie muscovite granites were generated by partial melting of Proterozoic meta-sediments, whereas the unmineralized Yuechengling biotite granites were derived from partial melting of Proterozoic meta-sediments with subordinate meta-igneous rocks. The unmineralized Yuechengling two-mica granites have similar geochemical characteristics to the mineralized Niutangjie muscovite granites, but their relatively small volumes and lack of exploration may explain why the Yuechengling two-mica granites have not so far been found to be mineralized. Similarly, the larger volume and more highly fractionated nature of the Mesozoic Yanshanian mineralized granites may explain the greater abundance of W-Sn mineralization associated with these rocks compared to the Paleozoic Kwangsian granite
Keywords: Kwangsian granites; Granite-related W mineralization; Niutangjie W deposit; South China Block